The empirical study of modal parameters of emotions in everyday life - Pacevičius, Jonas (Psichologija, 1998)
The method of longitudinal study of everyday emotions was used here. 77 Ss using special forms and experiment – based list of emotional terms had been registering their everyday emotions chronologically for two, three or four weeks. Individual and group data were obtained concerning the duration of four basic modalities of emotions (joy, anger, fear, grief) and tranquillity states, and their relations to the type of everyday activities. Inter-correlation analysis of modal and other emotional parameters (sign, intensity, stability) was carried out.
Keywords: emotions; basic emotions